Total haemoglobin mass but not cardiac volume adapts to long-term endurance exercise in highly trained spinal cord injured athletes - Schumacher, Y. O.; Ruthardt, S.; Schmidt, M.; Ahlgrim, C.; Roecker, K.; Pottgiesser, T. (European Journal of Applied Physiology, 2009)
The oxygen transport system is an important component in the limitation of endurance performance in able-bodied and paraplegic athletes. The aim of the present study was to investigate the total haemoglobin mass (tHb, carbon monoxide rebreathing method) and cardiac volume (HV, echocardiography) in 25 highly endurance trained male spinal cord injured (mainly paraplegic) athletes (SCI-TRAINED) and to compare the results with those of 10 untrained spinal cord injured controls (SCI-UNTRAINED) and in 25 able-bodied elite endurance athletes (TRAINED). tHb and tHb/kg were higher in SCI-TRAINED than in SCI-UNTRAINED (748 ± 110 vs. 629 ± 209 g (464 ± 68 vs. 390 ± 130 mmol) (mean ± SD), P = 0.02 and 10.3 ± 1.3 vs. 7.9 ± 2.0 g/kg (6.4 ± 0.8 vs. 4.9 ± 1.2 mmol/kg), P < 0.0001), while HV and HV/kg showed no significant differences between the two groups (765 ± 93 vs. 793 ± 164 ml and 10.6 ± 1.4 vs. 10.3 ± 2.5 ml/kg). No difference between SCI-TRAINED and TRAINED was found for septal diameter (9.5 ± 1.0 mm vs. 9.7 ± 0.7 mm). However, tHb and tHb/kg in SCI-TRAINED was lower than in TRAINED [896 ± 123 g (556 ± 76 mmol), P = 0.0003 and 12.6 ± 1.3 g/kg (7.8 ± 0.8 mmol), P < 0.0001]. In spinal cord injured athletes, tHb but not HV adapts moderately to chronic endurance exercise, although tHb in spinal cord injured athletes does not reach the level of able-bodied-trained persons.